Two‐Photon Luminescence and Second‐Harmonic Generation in Organic Nonlinear Surface Comprised of Self‐Assembled Frustum Shaped Organic Microlasers. Issue 15 (23rd January 2017) - Venkatakrishnarao, Dasari; Narayana, Yemineni S. L. V.; Mohaiddon, Mahamad A.; Mamonov, Evgeniy A.; Mitetelo, Nikolai; Kolmychek, Irina A.; Maydykovskiy, Anton I.; Novikov, Vladimir B.; Murzina, Tatiana V.; Chandrasekar, Rajadurai
Abstract : An ultrathin nonlinear optical (NLO) organic surface composed of numerous self‐assembled frustum‐shaped whispering‐gallery‐mode resonators displays both two‐photon luminescence and second‐harmonic‐generation signals. A super‐second‐order increase of the NLO intensity with respect to pump power confirms the microlasing action and practical usefulness of the NLO organic surfaces.